Genetic polymorphisms, concussion risk, and post concussion neurocognitive deficits in college and high school athletes. Issue 5 (11th March 2013) - Terrell, Thomas R; Bostick, Roberd M; Barth, Jeffery; McKeag, Douglas; Cantu, Robert C; Sloane, Rick; Galloway, Leslie; Erlanger, David; Valentine, Verle; Bielak, K
Abstract : Objective: To investigate associations of APOE and Tau gene polymorphisms with sports-related acute concussions and baseline to post-concussion neuropsychological test score changes. Design: Multi-center prospective cohort study. Setting: Scholarship athletes at 21 universities and 4 high schools Participants: 3218 athletes playing football (70%) or soccer (23%). Assessment of Risk Factors: APOE, APOE G-219T promoter (APOEProm), Tau exon 6 Ser53Pro (TauSer), and Tau exon 6 Hist47Tyr (TauHis) genetic polymorphisms. Main Outcome Measurements: (1) Acute concussions and (2) differences between baseline and 24–72 h post-concussion Headminder Neuropsychological Test Scores of Simple and Complex Reaction Time (SRT and CRT, respectively) and Processing Speed. Results: There were a total of 131 athletes with incident concussions and genetic data and neuropsychological test scores. There were no statistically significant differences in frequencies of acute concussions according to genotypes by χ 2 test. By t-test, the mean baseline to post-concussion neuropsychological changes were statistically significantly greater for CRT and SRT in those with the TauSer 'TT' genotype and for CRT in those with the APOEProm 'TT' genotype, and borderline significantly greater in those with the TauSer 'TT' genotype (p=0.09). Conclusions: The statistically significantly worse mean baseline to post-concussion neuropsychological test scores in those with the APOEProm and TauSer polymorphisms suggests a possible genetic influence on post-concussion neurocognitive recovery. These preliminary findings provide no evidence for associations of the four APOE and Tau gene polymorphisms investigated with acute concussions, although the small sample size and lack of control for confounders are limitations. Acknowledgements: Grant funding was provided through the NOCSAE (National Operating Committee for Safety Athletic Equipment) and the American Medical Society for Sports Medicine (AMSSM) Foundations. The opinions expressed in this abstract are not those of NOCSAE or AMSSM. Competing interests: None.